Southeast Asia's Cyber Security Strategy: Multilateralism or Self-help - Prawiyogi, Anggy Giri; Alwiyah (Pandawan Sejahtera Indonesia, 2023)
In terms of security research, cyber security is fundamentally a recent problem. When all facets of political, military, economic, social, and cultural life are connected to cyberspace, this problem occurs. Cyberterrorism, cybercrime, and cyberwar are all potential concerns in cyberspace. This threat cannot be separated from Southeast Asia, one of the main regions in the globe with a strong rate of economic expansion. This study aims to analyze the best approach for preserving cyber security in Southeast Asia. Neoliberalism and neorealism are common to mainstream methodologies scholars utilize to address the study subject. Simply put, ASEAN nations must advance their technology capacities while not underestimating the value of international cooperation.